2020
DOI: 10.1101/2020.09.29.314781
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Drought duration determines the recovery dynamics of rice root microbiomes

Abstract: As extreme droughts become more frequent, dissecting the responses of root-associated microbiomes to drying-wetting events is essential to understand their influence on plant performance. Here, we show that rhizosphere and endosphere communities associated with drought-stressed rice plants display compartment-specific recovery trends. Rhizosphere microorganisms were mostly affected during the stress period, whereas endosphere microorganisms remained altered even after irrigation was resumed. The duration of dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 78 publications
(93 reference statements)
0
5
0
Order By: Relevance
“…However, a succession of studies have now suggested that this difference in drought tolerance levels between varieties (genotypes) is partly due to rhizosphere microbial differences . Studies on sugarcane (Liu Q. et al, 2021), tomato (Gaete et al, 2021), cotton (Ullah et al, 2019), soybean (Kuzmicheva et al, 2017), rice (Santos-Medellin et al, 2017), and switchgrass (Liu T. Y. et al, 2021) have all supported this view. Host plants are able to alter rhizosphere microbial composition by influencing root structure and secretions (Wen et al, 2020), which, in turn, enhances plant resistance through rhizosphere interactions, although this effect varies widely among species and genotypes.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, a succession of studies have now suggested that this difference in drought tolerance levels between varieties (genotypes) is partly due to rhizosphere microbial differences . Studies on sugarcane (Liu Q. et al, 2021), tomato (Gaete et al, 2021), cotton (Ullah et al, 2019), soybean (Kuzmicheva et al, 2017), rice (Santos-Medellin et al, 2017), and switchgrass (Liu T. Y. et al, 2021) have all supported this view. Host plants are able to alter rhizosphere microbial composition by influencing root structure and secretions (Wen et al, 2020), which, in turn, enhances plant resistance through rhizosphere interactions, although this effect varies widely among species and genotypes.…”
Section: Introductionmentioning
confidence: 94%
“…For example, different core communities of rhizosphere microbiomes constructed from unique varieties of plants such as tomato (Adedayo et al, 2022), citrus (Penyalver et al, 2022), and wheat (Azarbad et al, 2018) were able to improve their environmental adaptability. Similarly, genetically diverse rice varieties respond to drought stress by using specific rhizosphere microbial communities (Santos-Medellin et al, 2017). Currently, most studies of plant-associated microbial communities have been conducted by means of ribosomal amplicon-based approaches (Glick and Gamalero, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, other biological and technical factors could explain why we detected few effects of PRRs on microbiome structure in the field. Myriad environmental conditions including temperature, humidity, soil salinity, phosphorus availability, and drought are known to modulate the strength of plant immunity and affect microbiome composition (Cheng et al, 2013;Castrillo et al, 2017;Naylor et al, 2017;Santos-Medellıń et al, 2017;Berens et al, 2019;Chen et al, 2020). Although the field conditions in our experiment were representative of Midwestern USA, an area in which A. thaliana is common (Platt et al, 2010;Exposito-Alonso et al, 2018;Shirsekar et al, 2021), it is possible that PRR signaling was rendered unimportant by environmental conditions.…”
Section: Discussionmentioning
confidence: 96%
“…The salinity-induced changes in rhizosphere microbial communities tend to promote Hibiscus hamabo germination and growth (Yuan et al, 2019). Drought triggered a compartmentspecific restructuring of rice root microbiota, with endosphere communities displaying a more pronounced response than rhizosphere communities (Santos-Medellin et al, 2017). Studies focusing on synthetic microbial communities have emerged, driven by the great application potential to provide sustainable agriculture solutions.…”
Section: Impact Of the Biocontrol Agent On The Endophytic Community F...mentioning
confidence: 99%